2020
DOI: 10.1016/j.jcf.2019.10.023
|View full text |Cite
|
Sign up to set email alerts
|

CFTR-deficient pigs display alterations of bone microarchitecture and composition at birth

Abstract: Background: The lack of cystic fibrosis transmembrane conductance regulator (CFTR) function causes cystic fibrosis (CF), predisposing to severe lung disease, reduced growth and osteopenia. Both reduced bone content and strength are increasingly recognized in infants with CF before the onset of significant lung disease, suggesting a developmental origin and a possible role in bone disease pathogenesis. The role of CFTR in bone metabolism is unclear and studies on humans are not feasible. Deletion of CFTR in pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The main effects of CFTR mutations are diminished ability to interact with other proteins and faulty chloride channel function, which ultimately influence bone cell differentiation [ 79 ]. CFTR deficiency alters porosity and chemical composition in the bones of newborn pigs [ 80 ], as well as reducing bone length, growth plate thickness, bone content and insulin-like growth factor-I in CFTR-knockout rats [ 81 ]. In patients with CF, CFTR mutation may impact NF-κB and Wnt signalling, resulting in disruption to osteoblast differentiation as well as decreased bone formation and increased bone resorption [ 79 , 82 ].…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…The main effects of CFTR mutations are diminished ability to interact with other proteins and faulty chloride channel function, which ultimately influence bone cell differentiation [ 79 ]. CFTR deficiency alters porosity and chemical composition in the bones of newborn pigs [ 80 ], as well as reducing bone length, growth plate thickness, bone content and insulin-like growth factor-I in CFTR-knockout rats [ 81 ]. In patients with CF, CFTR mutation may impact NF-κB and Wnt signalling, resulting in disruption to osteoblast differentiation as well as decreased bone formation and increased bone resorption [ 79 , 82 ].…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…Loss of CFTR protein or/and its chloride channel function has a detrimental impact on bone cells. Recent studies in CFTR-deficient new-born pigs showed high porosity of cortical bones and altered chemical composition of the trabecular bones (Braux et al, 2020). Cftr−/− mice display severe osteopenia in both trabecular and cortical bone (Dif et al, 2004).…”
Section: Effect Of Cftr Mutations On Canonical Wnt Pathwaymentioning
confidence: 99%
“…Regarding bones samples, the number of CFU was correlated with the weight of the samples after determination of a linear correlation between weight and available bone surface using micro-computed tomography (Skyscan 1076, Bruker Optics, Germany) ( Supplementary Fig. S2 ) [ 30 ]. For each experiment, at least four biological repeats were performed.…”
Section: Methodsmentioning
confidence: 99%